Lipoprotein(a) Induces Vesicular Cardiovascular Calcification Revealed With Single-Extracellular Vesicle Analysis - Rogers, Maximillian A.; Atkins, Samantha K.; Zheng, Kang H.; Singh, Sasha A.; Chelvanambi, Sarvesh; Pham, Tan H.; Kuraoka, Shiori; Stroes, Erik S. G.; Aikawa, Masanori; Aikawa, Elena (Frontiers in Cardiovascular Medicine, 2022)
Lipoprotein(a) (Lp[a]) blood levels >50 mg/dL is a major cardiovascular disease risk factor in humans. Lp(a) associates with increased cardiovascular calcification, a critical pathology with no clinically available drug therapies. The mechanisms through which Lp(a) increases cardiovascular calcification risk remain undefined. We hypothesized that Lp(a) promotes the release of calcifying extracellular vesicles (EVs) that contribute to formation of microcalcification in cardiovascular tissues. Here, we show Lp(a) increased calcification in both primary human smooth muscle cells (SMCs) and valvular interstitial cells (VICs), potentially through inflammation-related mechanisms that were suppressed with E06 antibody that neutralizes pro-inflammatory oxidized phospholipids. Incubating human SMCs and VICs with Lp(a) altered the composition of EVs, increasing CD29+/tetraspanin− microvesicle release, demonstrated with a tailored single-EV microarray assay that can distinguish multivesicular body-derived exosomes and plasma membrane budded microvesicles at a single-vesicle level. Lp(a) stimulation led to release of SMC and VIC EVs that readily calcified in acellular 3D-collagen hydrogels mimicking formation of ectopic microcalcification occurring in extracellular matrix of human atherosclerotic arteries and stenotic aortic valves. Our study mechanistically demonstrates that Lp(a) partially mediates cardiovascular calcification formation via inducing the release of calcifying EVs. Additionally, we provide a customized method to assess calcifying EVs at a single-vesicle level that can be more broadly applied to assist in quantitatively differentiating exosome and microvesicle EV subpopulations.